Performance Assessment of Efficiency and Productivity of Indonesian Micro Waqf Banks - Aspiranti, Tasya; Shaharuddin, Amir; Amaliah, Ima (KnE Social Sciences, 2024)
In the observation period from 2018 to 2021, the growth of outstanding financing only grew 6.5% per year and the number of outstanding customers grew 4.91% per year, while the number of stagnant micro waqf banks did not grow at 62. Therefore, it is urgent to measure the efficiency and productivity of micro waqf banks so that the source of the causes of the suboptimal distribution of micro waqf bank financing to the community around the pesantren can be evaluated. Technical analysis with DEA and Malmquist Index was used to measure the efficiency and productivity. The input data used are the number of outstanding customers, the number of Kumpi, and the number of micro waqf bank offices. Output data uses the amount of outstanding financing. Micro waqf banks that have consistently been inefficient from 2018 to 2021 are waqf banks in Riau and West Java Provinces. The inefficient waqf bank according to this approach is only 27.75. Overall, micro waqf banks have very low technological innovation. Optimization of micro waqf bank financing can still be done by optimizing the function of micro waqf banks and activating micro waqf bank partners who have been passive. Keywords: efficiency, productivity, technology, Waqf Bank